2020
DOI: 10.1111/jvim.15997
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of minimally invasive imaging techniques to assess intestinal mucosal perfusion with established markers of chronic inflammatory enteropathy in dogs

Abstract: Background: Minimally invasive diagnostic imaging techniques to detect intestinal inflammation in dogs are lacking. Contrast-enhanced ultrasound (CEUS) and endoscopic narrow band imaging-like endoscopy (Storz Professional Image Enhancement System [SPIES]) might allow quantification of intestinal mucosal perfusion and microvessel density in chronic inflammatory enteropathy (CIE) of dogs. Hypothesis/Objectives: Markers of mucosal perfusion as determined by CEUS and SPIES endoscopy are potentially useful diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The pigs were eventually euthanized to obtain tissue samples and pathological specimens. Compared with the sacrificing of animals, the application of endoscopy in research studies is considered a minimally invasive and more humane method, along with assessing the intestinal condition of the animals and obtaining tissue specimens (35)(36)(37).…”
Section: Improved Model Of Mechanically Induced Porcine Arfmentioning
confidence: 99%
See 1 more Smart Citation
“…The pigs were eventually euthanized to obtain tissue samples and pathological specimens. Compared with the sacrificing of animals, the application of endoscopy in research studies is considered a minimally invasive and more humane method, along with assessing the intestinal condition of the animals and obtaining tissue specimens (35)(36)(37).…”
Section: Improved Model Of Mechanically Induced Porcine Arfmentioning
confidence: 99%
“…Due to the complex animal ethics and experimental methodology, only a small number of studies have been performed using canine models. It has been suggested that endoscopy should be used in experiments with large animals, as it is simple and may reduce the level of trauma to animals (35,37). Furthermore, endoscopy may be used repeatedly to obtain a more accurate assessment of the disease status.…”
Section: Canine Model Of Human Fistulizing CDmentioning
confidence: 99%
“…CE allows an enhancement of mucosal surface patterns, color, and vascularization, inducing a paradigm shift from random to targeted biopsies in patients with subtle gastric mucosal changes [ 7 ]. Examples of such novel imaging technologies are narrow band imaging (NBI), Storz professional image enhancement system (SPIES), and flexible spectral imaging color enhancement, all using specifically developed endoscopy equipment [ 8 , 9 , 10 ]. Studies in humans revealed that, for example, NBI allows the identification of gastric mucosal patterns with high predictive value for the final histologic diagnosis of normal mucosa (83%), intestinal metaplasia (84%), and dysplasia (95%) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It remains rather challenging to predict the possible mucosal pathology and to detect preneoplastic processes and malignancies early and accurately, especially when they are still subtle and confined to the gastric mucosa [ 1 ]. Despite the increased availability of CE equipment in veterinary medicine, there have been only very few studies exploring the possibilities of CE for canine and feline patients [ 9 , 14 ]. It remains so far uncertain whether CE techniques can improve the diagnostic yield of endoscopy in dogs.…”
Section: Introductionmentioning
confidence: 99%